Male pseudohermaphrodite with persistent Mullerian duct: A radiologist's and patient's dilemma alike. (23rd December 2020) - Kaur, Ravinder; Kaur, Arshpreet; Vermani, Sanya
Abstract: This case study highlights that how a disorder of sexual development when goes unnoticed at birth and unreported during childhood or adolescence can present with major problems and even complications in adulthood. Since our patient was young and in a childbearing age, he presented with bilateral undescended testes and orgasmic anejaculation when he first came to the hospital. Subsequently, having a normal 46XY karyotype but remnants of persistent Mullerian duct made him little confused about his identity. After giving him the confidence, that he was still a male and could lead the life he did previously, the explanation about future risk of malignancy in the intra‐abdominal testes was another difficult task. Early detection and management of male pseudohermaphroditism with persistent Mullerian duct requires a co‐ordinated approach of a team of endocrinologist, physician, surgeon and radiologist. Integrated imaging in the form of ultrasound, genitography and MRI is important in demonstrating the anatomy, classification, possible effects or congenital malformations in other organs, warning patients of any risk of neoplasia and guiding the clinician to plan other investigations, hormonal replacement or reconstruction surgery if required. Such a systemic approach that allays anxiety and gives psychological relief to the patient should be taken as it can deeply change the life of a person and their family.